Has the multilateral Hong Kong Ministerial decision on duty free quota free market access provided a breakthrough in the Least developed countries' export performance? - Sèna Kimm Gnangnon; Shishir Priyadarshi (World Trade Organization (WTO), 2016)
This paper assesses the impact of the 2005 multilateral Hong Kong Ministerial decision on duty free quota free (DFQF) market access for products originating in Least developed countries (LDCs) on the latter's export performance. The analysis is conducted over a sample of 41 LDCs, with data spanning the period 1998-2013. The empirical analysis examines both the average effect and the short term/medium term effect. Results indicate that on average, this multilateral decision has exerted a positive effect on LDCs' performance on merchandise exports, with this average positive effect being solely driven by a positive effect on LDCs' export performance on primary products; the average effect on manufacturing exports has been statistically nil. In the short and medium term, this decision has exerted a positive effect on LDCs' merchandise export performance, as well as on the components of the latter, namely both primary product exports and manufacturing exports. However, the positive effect on primary product exports appears to be far higher than that on manufacturing exports. These findings have important policy implications regarding reflections on the way LDCs could utilize their policy flexibilities in the WTO Agreements to diversify their exports away from the primary sector and toward manufacturing and/or services sector.
Keywords: F13; F14; F15; F40; 330; Multilateral Hong Kong Ministerial Decision on DFQF; Export Performance; Least Developed Countries